Tribological evaluation of refined, bleached and deodorized palm stearin using four-ball tribotester with different normal loads - Tiong, Chiong Ing (SP Zhejiang University Press, 2012)
The effects of the mechanical factors with applied loads on the tribological performance of refined, bleached and deodorised (RBD) palm stearin (PS) were studied using a four-ball tribotester. All the RBD PS results were simultaneously compared with the additive-free paraffinic mineral oil (PMO). The experiments were carried out using different loads with a constant speed in order to gain a better understanding of the mechanical processes that occurred during the experiment. For each experiment, the temperature was increased to 75 °C and was run for 1 h. In a mechanical system, lubricant plays an important role in reducing wear and friction. PS exists as a semi-solid at room temperature after the fractionation process from oil palm. Due to the increasing rate of pollution to the environment, vegetable oil was chosen as the test lubricant with regard to its biodegradability. Other advantages of vegetable oil are that it is more easily harvestable and non-toxic compared to petroleum-based oil, which made it a suitable candidate. From the experiment, RBD PS is found to have a better friction constraint reduction compared with additive-free PMO.